Inequalities in oral health: results from the First Portuguese National Health Examination Survey - Antunes, Liliana (2017)
Oral health is a state of being free from a range of diseases and disorders that affect oral cavity. Dental cavities and gum diseases are among the most prevalent diseases worldwide. However, they can be prevented as risk factors include poor diets and hygiene. Also, social determinants play a key role as it is well established that poor health is higher among the most disadvantaged. Thus this study aimed to describe oral preventive care of the Portuguese population and assess socioeconomic inequalities.